EFEKTIFITAS KOMUNIKASI PROYEK KONSTRUKSI SAAT PANDEMI DARI SUDUT PANDANG KONTRAKTOR - Ryan Faza Prasetyo; Rama Adjie Darmawan (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2023)
Project communication management is an effort to ensure timeliness, collection and distribution of information according to the times. The level of success of a project has to do with Critical Success Factor (CSF) and one of them is communication. 2020 was a year that changed people's lives around the world because of the COVID-19 pandemic and had an impact on the construction sector in Indonesia. The PUPR Ministry issued Ministerial Instruction No. 02/IN/M/2020 regarding the mechanism for carrying out construction in preventing the spread of COVID-19 in both the government, regional government, BUMN, and private sectors during a pandemic (Construction Bulletin, 2020). In this case the implementation of Work Form Home (WFH) in contractor companies is one of the efforts to minimize the spread of the virus and continue to run the wheels of the economy (Prasetyo, 2022). This study aims to determine whether or not there is an influence on the effectiveness of the communication coordination relationship due to the COVID-19 pandemic in the construction process and to analyze whether or not there is a difference in the effectiveness of the communication coordination relationship before the pandemic and during the pandemic from the contractor's point of view. The research was conducted by distributing questionnaires to contractor stakeholders. Research data processing was carried out using excel and SPSS software. Data analysis was performed using descriptive statistics and comparative analysis.